TREND SEMI AVERAGE AND LEAST SQUARE IN FORECASTING YAMAHA MOTORCYCLE SALES - Ines Saraswati Machfiroh; Widiya Astuti Alam Sur; Robby Tri Pangestu (Barekeng)
This study compared the Semi Average and Least Square methods to determine the sales trend of Yamaha motorcycles in obtaining the best method for predicting motorcycle sales at CV Surya Prima Pelaihari. Mean Absolute Percentage Error (MAPE) was used to determine the accuracy of the Semi Average and Least Square methods in predicting the sales of CV Surya Prima Pelaihari motorbikes. Semi Average method was based on the MAPE value of 43.96%. The Least Square method has a MAPE value of 31.89%. The comparison of MAPE values shows that the Least Square method provides better predicting results because of the lower MAPE value. Therefore, the Least Square method was used to predict sales at CV Surya Prima Pelaihari. A more accurate output can be obtained than the Semi Average method.